Ian Marchant: The Battle for Dole Acre - Jaine, Tom (Petits Propos Culinaires, 2024)
Ian Marchant: The Battle for Dole Acre: Weidenfeld & Nicolson, London, 2001: ISBN 0-575-07205-7: 342 pp., p/b, £9.99.